A comprehensive guide to experimental and predicted thermodynamic properties of phosphate apatite minerals in view of applicative purposes. (February 2015) - Drouet, Christophe
Graphical abstract: Experimental thermodynamic properties of phosphate apatites are reviewed and commented. Predictive methods are developed and tested here for apatite compounds, allowing reliable estimations of Δ H f °, Δ G f ° and S °, not only for end-members but also for solid solutions, non-stoichiometric and hydrated samples. A periodic table of recommended thermodynamic properties for 33 apatite systems is generated, and relative stabilities are pointed out. Highlights: Experimental thermodynamic properties of phosphate apatites are reviewed. Predictive thermodynamic methods are investigated for estimating missing data. An additive model is developed to estimate Δ H f °, Δ G f ° and S ° for phosphate apatites. End-members, solid solutions, nonstoichiometric and hydrated samples are considered. A periodic table of recommended thermodynamic properties for 33 systems is proposed. Abstract: Apatite minerals represent a major class of ionic compounds of interest to many disciplines including medical sciences, geology, anthropology, cosmology, environmental and nuclear sciences. Yet, these compounds have not received great attention from a thermodynamic viewpoint, and some diverging data – often drawn from molecular modeling assays – were reported. In this contribution, an extensive literature overview of available experimental-based data on M10 (PO4 )6 X2 apatites with M = Ca, Ba, Sr, Mg, Cd, Pb, Cu, Zn and X = OH, F, Cl or Br has first been made, on the basis of standard formation energetics ( Δ H f ° and Δ G f ° ) as well as entropy S° and molar heat capacity C p, m ° . The case of oxyapatite was also included. From this overview, it was then possible to identify general tendencies, evidencing in particular the primary role of electronegativity and secondarily of ionic size. Using the experimental data as reference, several predictive thermodynamic methods were then evaluated, including the volume-based-thermodynamics (VBT) method and a more advanced additive contributional model. In particular, the latter allowed obtaining estimates of thermodynamic data of phosphate apatites within a maximum of 1% of relative error, generally within 0.5%. Fitted hi, gi and si contributive parameters are given for bivalent cations and monovalent anions, so as to derive, by simple summation, coherent estimates of Δ H f °, Δ G f ° and S° for any apatite composition, at T  = 298 K. The model was shown to also lead to consistent estimates in cases of solid-solutions or even non-stoichiometric or hydrated phosphates apatites. Ultimately, a periodic table of recommended thermodynamic properties of 33 phosphate apatites end-members (at T  = 298 K and 1 bar) was established, with the view to serve as an easily readable reference database.